Modern Greek Theologians and the Greek Fathers - Russell, Norman (Philosophy & theology, 2006)
For several centuries after the fall of Constantinople, Greek theological writing was dominated by an arid scholasticism. This paper seeks to show how since the Second World War modern Greek theologians, with the help of a number of diaspora theologians and Western patristic scholars, have re-engaged with the Greek Fathers. Four theologians are discussed in some detail: Gontikakis, Nellas, Yannaras and Zizioulas. Each emphasizes a different strand of patristic tradition, but all four share a sense of the Fathers as living witnesses to divine-human communion. Yannaras and Zizioulas have also brought to their interpretation of the Fathers some of the insights of modern existentialist philosophy. Although criticized by some, this approach has led to some important thinking on the nature of person and relation.